2005
DOI: 10.1104/pp.104.058065
|View full text |Cite
|
Sign up to set email alerts
|

Citrate Secretion Coupled with the Modulation of Soybean Root Tip under Aluminum Stress. Up-Regulation of Transcription, Translation, and Threonine-Oriented Phosphorylation of Plasma Membrane H+-ATPase

Abstract: The aluminum (Al)-induced secretion of citrate has been regarded as an important mechanism for Al resistance in soybean (Glycine max). However, the mechanism of how Al induces citrate secretion remains unclear. In this study, we investigated the regulatory role of plasma membrane H 1 -ATPase activity and expression were higher in an Al-resistant cultivar than in an Al-sensitive cultivar. Al activated the threonine-oriented phosphorylation of plasma membrane H 1 -ATPase in a dose-and time-dependent manner. Take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
117
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 150 publications
(124 citation statements)
references
References 68 publications
7
117
0
Order By: Relevance
“…In Al-resistance soybean roots, while FC or VA significantly enhanced or inhibited activity of the plasma membrane H C -ATPase by approximately 85% or 53%, Al-induced citrate exudation also increased or decreased about 58% or 52%, respectively. 9 In broad bean and Tamble balck soybean roots, the activity of plasma membrane H C -ATPase exhibited a significant linear correlation with the rates of citrate exudation both in Alresistance and Al-sensitive cultivars. [30][31][32][33] Furthermore, activation of the plasma membrane H C -ATPase is also involved in micromollar concentrations of magnesium (Mg) enhancement of Alinduced citrate exudation in ricebean and broad bean roots.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…In Al-resistance soybean roots, while FC or VA significantly enhanced or inhibited activity of the plasma membrane H C -ATPase by approximately 85% or 53%, Al-induced citrate exudation also increased or decreased about 58% or 52%, respectively. 9 In broad bean and Tamble balck soybean roots, the activity of plasma membrane H C -ATPase exhibited a significant linear correlation with the rates of citrate exudation both in Alresistance and Al-sensitive cultivars. [30][31][32][33] Furthermore, activation of the plasma membrane H C -ATPase is also involved in micromollar concentrations of magnesium (Mg) enhancement of Alinduced citrate exudation in ricebean and broad bean roots.…”
mentioning
confidence: 99%
“…34 Furthermore, 50 and 70 mM Al inhibited the plasma membrane H C -ATPase activity in wheat and soybean roots, respectively. 9,35 Furthermore, other authors reported that the enhanced release of H C and the activity of plasma membrane H C -ATPase did not coincide with increased exudation of carboxylate anions in tomato plant under Al stress. 36 and tomato, wheat and soybean under P deficiency conditions, respectively.…”
mentioning
confidence: 99%
See 3 more Smart Citations